2019
DOI: 10.1186/s12885-019-5509-4
|View full text |Cite
|
Sign up to set email alerts
|

Reduced FRG1 expression promotes prostate cancer progression and affects prostate cancer cell migration and invasion

Abstract: Background Prostate cancer is the most common form of cancer in males and accounts for high cancer related deaths. Therapeutic advancement in prostate cancer has not been able to reduce the mortality burden of prostate cancer, which warrants further research. FRG1 which affects angiogenesis and cell migration in Xenopus, can be a potential player in tumorigenesis. In this study, we investigated the role of FRG1 in prostate cancer progression. Methods Immunohistochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…Many studies have demonstrated its involvement in tumorigenesis and tumor progression: FRG1 mutations occur in patients with thyroid cancer and calcifying fibrous tumor of pleura 36 , 37 . Functionally, FRG1 may act as tumor suppress gene since its expression is reduced in various types of tumor, such as prostate, breast, lung, gastric, etc 38 , 39 . Further, FRG1 knockdown can lead to significantly enhanced invasion and migration abilities of tumor cells 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated its involvement in tumorigenesis and tumor progression: FRG1 mutations occur in patients with thyroid cancer and calcifying fibrous tumor of pleura 36 , 37 . Functionally, FRG1 may act as tumor suppress gene since its expression is reduced in various types of tumor, such as prostate, breast, lung, gastric, etc 38 , 39 . Further, FRG1 knockdown can lead to significantly enhanced invasion and migration abilities of tumor cells 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The expression of SP8 was decreased in primary gastric cancer compared with normal gastric mucosa in a recent study (Chang et al, 2009). FRG1 expression was decreased in PCa tissues and that affected the migration and invasion of cancer cells (Tiwari et al, 2019). Deleterious mutations of FRG1, which had been identified in calcified pleura fibrous tumor and follicular thyroid cancer, were suggested to contribute to tumorigenesis (Erinjeri et al, 2018;Mehrad et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…However, recent studies have demonstrated the role of FRG1 in tooth germ development and angiogenesis [6,22]. Our group has revealed its role in tumor development [7]. Being part of the spliceosomal C complex, FRG1's downregulation might lead to instability and disruption in downstream processes affecting the normal mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…FRG1 affected the proliferation, migration, invasion, and angiogenic potential of cancer cell lines and the expression of G-CSF and MMP10 [6]. Reduced FRG1 expression in AR negative prostate cancer cell lines increased invasiveness and cell migratory properties [7].…”
Section: Introductionmentioning
confidence: 99%